Assing value to Theobroma grandflorum for the preparations of handmade ince cream (Research, Society and Development, 2022)
Commercially available ice cream is generally poor in natural antioxidants, and it is interesting to explore possibilities that tend to improve the nutritional attributes of ice cream and add value to the product. In view of the above, the objective of this work was to promote the aggregation of value to cupuaçu (Theobroma grandfolium) through the elaboration of artisanal ice cream with different concentrations of the pulp. The experimental design used was completely randomized, consisting of the development of four ice cream formulations (10%, 15%, 20% and 35% cupuaçu pulp concentration), with five replications, totaling 20 experimental units. The treatments during and after processing were submitted to physicochemical, sensory and microbiological analyses. The results allowed us to conclude that the physicochemical analyses of the raw material present within the appropriate range for the production and aggregation of value to the cupuaçu. The addition of 15% cupuaçu pulp allows reduction in total acidity, increase in °Brix and sensory attributes of color and texture, conferring greater acceptability by the consumer; while the addition of 35% cupuaçu pulp to ice cream showed lower overall aspect evaluation and purchase intention. The processing of ice cream in the presence of cupuaçu fruit pulp is characterized as an opportunity for diversification and value aggregation to production, improvement in the development of regional products and guarantee of food and nutritional safety, respecting microbiological quality standards.